HUBUNGAN PERANAN KEPEMIMPINAN DENGAN MOTIVASI KERJA STAF DI PUSKESMAS MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - Anisa Manopo; Theo W E Mautang; Prycilia P Mamuaja (JURNAL ILMIAH KESEHATAN MANADO, 2024)
The role of leadership in an organization plays a major role in running a health organization in order to achieve optimal and sustainable health development goals. The purpose of motivation in the workplace is to improve employee morale and job satisfaction, improve work results, encourage discipline and minimize absenteeism, foster a positive work environment and relationships, stimulate creativity and involvement, improve welfare, instill a sense of responsibility for work and optimize the efficiency of tool utilization. The purpose of this study was to determine the relationship between the role of leadership and staff work motivation at the Motoling Timur Health Center, South Minahasa Regency. This study was conducted using a quantitative method with a cross-sectional approach. The sample of this study was 19 people who were taken through total sampling. Using non-parametric techniques and chi-square analysis data. Research Results Most respondents, namely 13 respondents (68.4%) who assessed that the role of leadership with work motivation at the Motoling Timur Health Center, South Minahasa Regency was in the good category. The results of statistical tests using the relationship between the role of leadership and staff work motivation had a p value = 0.004. Conclusion There is a relationship between the role of leadership and employee work motivation at the Motoling Timur Health Center, South Minahasa Regency.